Structure and activation of endothelin ETB receptor by endothelin - Doi, Tomoko (Henry Stewart Talks, 2019)
Background to endothelin, ET(A) and ET(B), Endothelin and peptide GPCR, Vasoactive and mitogen-like peptide, Thermostabilization of ET(B), Structures of ET-1-bound and bosentan-bound ET(B) receptor, Ligand recognition and conformational changes of ET(B) for signal transduction